HUBUNGAN POWER OTOT LENGAN DAN BAHU TERHADAP HASIL TOLAK PELURU GAYA ORTHODOX SISWA PUTRA KELAS XI ILMU ILMU SOSIAL5 SMA N 2 TUALANG - Johanes, Boyke; Saripin, Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is whether there is a relationship of muscle power of arm and shoulder on the result of shot put with orthodox style male student of class XI Ilmu Ilmu Sosial5 SMA N 2 Tualang. The goal is to find out how big the muscle power of arm and shoulder on the result of shot put with orthodox style male student of class XI Ilmu Ilmu Sosial5 SMA N 2 Tualang singly. The technique of sampling performed with total sampling of 16 male students of class XI Ilmu Ilmu Sosial5 SMA N 2 Tualang. This research using a correlation technique. Then, the data are tested using the test of normality, test the product moment correlation test, test of significance on the level of significance of α = 0.05. Test of normality of variabels X, L0maks (0,0966) < Ltabel (0,213), and testing normality of variabels Y, L0maks (0,1728) < Ltabel (0,213) in other words at a confidence level of 95% of normal data and concluded the results showed: there is a significant relationship between on muscle power of arm and shoulder on the result of shot put with correlation r= 0.6709, where rhitung > rtabel or 0.6709 > 0,514. and such relations are categorized strong. Thus, Ha accepted.Key word : relationship, muscle power of arm and shoulder, the result of shot put.